Petal-shaped SnO2 free-standing electrodes with electrically conducting layers via a plasma-activated nitrogen doping process for high performance lithium-ion batteries - Shin, Hyun-Jin; Kim, Tae Hyun; Abbas, Saleem; Cho, Jinhan; Ha, Heung Yong (ELSEVIER SCIENCE SA, 2021)
SnO2 Free-standing anodes are regarded as a potential negative electrode for high energy lithium ion batteries (LIBs). However, they suffer from poor rate capability and reversibility because of very low electric conductivity of SnO2. In this study, in order to endow electrical conductivity to the surface of SnO2 particles, a novel and facile method using a plasma are employed to dope nitrogen into the lattice of SnO2. The SnO2 free-standing anode was fabricated by carbonizing an electro-spun fiber sheet followed by depositing SnO2 particles on the surface of carbon nanofibers (CNF) comprising the sheet through a hydrothermal process. The best N-doped SnO2 anode obtained under an optimized condition exhibits a 23 times higher specific capacity of 767 mAh g(-1) than that of a pristine SnO2 anode (<32 mAh g(-1)) at a high current density of 3.0 A g(-1). Furthermore, in a long-term cycle test at 0.1 A g(-1), this anode shows a high retention capability with a specific capacity of 909 mAh g(-1) and Coulombic efficiency (CE) of 99.3% after 100 cycles. Based on the extensive physical/electrochemical characterizations and performance tests, a mechanism is proposed explaining the roles of N-doped SnO2 layer in the electrochemical reactions. Overall, the plasma-treated SnO2 anode exhibits significantly improved capacity retention, rate capability and long-term cycle stability by forming an electrically conducting layer on the surfaces of SnO2 particles. Therefore, this plasma technique is confirmed to be a very facile and effective way to significantly improve the performance of SnO2 anode for LiBs.